Hubungan Lembaga Eksekutif dan Legislatif Dalam Penyusunan Rancangan APBD di Kabupaten Bulukumba - A. Faizul Fahri (Departemen Ilmu Pemerintahan Fisip Unhas, 2026)
The relationship between the executive and legislative institutions is a crucial factor in developing an effective, transparent, and accountable Regional Revenue and Expenditure Budget (APBD). In the practice of local governance, the budget formulation process often faces various institutional dynamics influenced by differences in interests, information asymmetry, and suboptimal oversight mechanisms. This study aims to analyze the institutional relationship between the executive and legislative branches in the formulation of the Regional Revenue and Expenditure Budget Draft (RAPBD) in Bulukumba Regency from the perspective of Agency Theory. This research employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving informants from the Bulukumba Regency Government and the Regional House of Representatives (DPRD). Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the institutional relationship between the executive and legislative branches in the RAPBD formulation process is influenced by four main aspects: information asymmetry, supervision and control, transparency, and accountability. Information asymmetry remains evident due to the executive's dominance in accessing and controlling budget-related information. Supervision and control exercised by the DPRD play a significant role in maintaining institutional balance, although several challenges persist in their implementation. Transparency in the budgeting process has been carried out through budget deliberation mechanisms; however, greater public access to information is still required. Meanwhile, accountability serves as a fundamental instrument in ensuring that regional financial management complies with existing laws and regulations.